Museums of Anthropology or Museums as Anthropology? - Pearce, Susan M. (Anthropologica, 2022)
During 1995 the Pitt Rivers Museum, University of Oxford, marketed a postcard depicting 14 early handwritten labels from the museum's archive. This commercially orientated, self-reflexive museum production is taken as the starting point for an analysis of the relationship between the collection, the collector, the museum exhibition and the visiting public. The roles of documentation as an aspect of colonial appropriation, and that of artists in residence as parallel commentary are reviewed.